Financial crisis impact on the efficiency evaluation of university research achievements transformation: a study based on fixed and interactive network data envelopment analysis methods - Ma, Yuping; Xu, Mingqian (Frontiers in Physics, 2025)
In the context of the financial crisis, this paper introduces an innovative approach to Data Envelopment Analysis (DEA) that is grounded in collaborative theory, aiming to assess the impact of financial factors, particularly fiscal allocations, on the efficiency of transforming research achievements into practical applications within Chinese universities. Based on this methodological framework, the paper constructs an interactive network framework that integrates government, industry, and academic institutions, conceptualizing research activities as a multi-agent, multi-stage complex system. Through an empirical analysis of 79 Chinese universities, we investigate the role of government fiscal grants as a key input factor in influencing the efficiency of research achievement transformation within this system. The findings reveal that strategic allocation of fiscal grants significantly enhances the efficiency of research application, while substantial variations in the efficiency of research achievement transformation exist across different universities. This study further elucidates the intrinsic link between fiscal allocations and the commercialization efficiency of research achievements, providing policymakers with critical insights into the effective distribution of financial resources to facilitate the transformation of research achievements into practical applications. This research not only enriches the application of complex systems theory in higher education but also offers a novel perspective on the role of financial support policies in the commercialization of scientific and technological achievements.